Description of renal function in type 2 DM patients at RSU Royal Prima Medan in 2022 - Anita Merry Cisca; Yosep Primus Tafonao; Suhartina, Suhartina (Jurnal EduHealth, 2024)
One of the chronic microvascular complications that occurs in type 2 DM patients is diabetic nephropathy, which is a condition where the kidneys experience decreased function and damage to the blood filter membrane is caused by high blood sugar levels. The aim of this study was to determine the description of kidney function in type 2 diabetes mellitus patients by looking at the glomerular filtration rate from medical record data of type 2 diabetes mellitus patients at RSU Royal Prima Medan. This type of research is descriptive observational research, the population in this study is the medical records of patients with type 2 diabetes mellitus who received treatment at RSU Royal Prima Medan in 2022 with a sample size of 34 medical records of patients with type 2 diabetes mellitus who received treatment at RSU Royal Prima Medan in 2022. 2022. Data analysis using univariate analysis. The results of the study showed that the frequency of Type 2 DM at RSU Royal Prima based on age was 5.9% of patients aged 35 - 45 years and 94.1% aged > 45 years. The frequency of Type 2 DM at RSU Royal Prima based on gender was found to be 52.9% for males and 47.1% for females. The frequency of Type 2 DM at RSU Royal Prima based on the duration of suffering from Type 2 DM was found to be 2.9% of patients with a duration of suffering < 1 year, 29.4% of patients with a duration of suffering of 1 - 5 years and patients with a duration of suffering > 5 years as many as 67.6%. Presentation of Type 2 DM Renal Function based on the age of 34 patients, the majority of GFR values were in the moderately declining GFR category for patients aged > 45 years as many as 19 (55.9%) patients. Presentation of Type 2 DM Kidney Function based on gender, the GFR value in patients based on gender of the 34 patients, the majority were in the moderately decreased GFR category in patients with female gender, 10 (29.5%) patients. Presentation of Kidney Function of Type 2 DM based on the length of time they have suffered from Type 2 DM, the GFR value in patients based on the length of time they have suffered from Type 2 DM out of 34 patients, the majority of them are in the GFR category of moderate decline in patients with a duration of suffering from DM > 5 years, 19 (55.9 %) patients.